COVID-19 Vaccination Rates in a Cohort Study of Patients With Mental Illness in Residential and Community Care - Mazereel, Victor; Vanbrabant, Tom; Desplenter, Franciska; Detraux, Johan; De Picker, Livia; Thys, Erik; Popelier, Ken; De Hert, Marc (Frontiers in Psychiatry, 2021)
Background: Patients with mental illness are at increased risk for COVID-19-related morbidity and mortality. Vaccination against COVID-19 is important to prevent or mitigate these negative consequences. However, concerns have been raised over vaccination rates in these patients. Methods: We retrospectively examined vaccine uptake in a large sample of Belgian patients admitted to or residing in a university psychiatric hospital or community mental health care setting between 29th of March 2021 and 30th of September 2021 in the Flanders Region. All patients were offered vaccination. Descriptive statistics were used to analyse the data. Logistic regression was used to examine factors associated with vaccine uptake. Results: 2105 patients were included in the sample, of which 1931 agreed to be vaccinated, corresponding with a total vaccination rate of 91.7%. Logistic regression showed an effect of the diagnosis ‘other disorders’ (OR=0.08, CI=0.005-0.45), age (OR=1.03, CI=1.02-1.04) and residing in the psychosocial care center (OR=0.50, CI=0.32-0.80) on vaccination status. Conclusion: Vaccine uptake among people with mental illness is high and comparable to the general population, when implementing a targeted vaccination program.